Factors affecting financial management to support students facing finance difficulty at the universities in zhejiang province - Hongping , Cao; Siththada , Thada (Journal of Roi Kaensarn Academi, 2024)
This study is about the influencing factors of financial management supporting economically disadvantaged students in Zhejiang University. The sample used in this study were administrators and faculty of Zhejiang University. A total of 109 universities in Zhejiang province used 55 universities in Zhejiang Province, and the sample size was determined by the schedule of Chris and Morgan. The researchers assigned 5 respondents to each university, including 2 school administrators (100 respondents) and 3 teachers (300 respondents), for a total of 300 respondents using simple random sampling. According to the Likert concept, the study instrument is a 5-grade questionnaire. The questionnaire was divided into three parts, including the first part: the respondents’ personal identity information was gender, age, highest education, and experience in the current position. Part 2: Factors affecting financial management, including 44 questions, which are divided into 7 aspects, namely, money attitude, economic literacy, consumption view, factors influencing financial literacy, family economic literacy, individual money management ability, and individual financial awareness. Part 3: Financial management, to support students to face financial difficulties, a total of 27 problems, divided into five aspects, namely, university financial budget management, university financial financing, tuition and miscellaneous fees collection, loan risk, financing risk. The reliability of the questionnaire was determined by determining the α coefficient with a confidence of 0.993. Statistics used to analyze the data are frequency, percentage, and mean. Standard deviation of mean Pearson coefficient correlation Coefficient and Stepwise Multiple gression Analysis, investigators summarize the findings, discuss results and recommendations.